Assessment of e-commerce adoption benefits by Indonesian women entrepreneurs - Kartiwi, Mira; Gunawan, Teddy Surya (2013)
The importance of the small to medium enterprise (SME) sector as the cornerstone of most economies is widely recognised. This is not only borne out by the number of SMEs (almost 90% of the total number of businesses across the world), but also by their significant role in creating employment opportunities. SMEs are considered to be the only realistic employment opportunity for those in lower income brackets, especially women in developing countries. However, studies also show that there are inherent issues impede the growth of female-owned SMEs, particularly those in rural areas in developing countries. Among others are the difficulties in accessing financial assistance to set up a business, the child-rearing obligation which limits women’s mobility and access to information of the available market. Electronic commerce (e-commerce), on the other hand, has radically changing the dynamics of the business environment and the way in which people and organizations are conducting business with one another. For SMEs, e-commerce has the potential to become a source of competitive advantage. E-commerce is a cost effective way of accessing customers globally and competing on par with large businesses. Despite the many benefits of e-commerce, little research has been done to investigate the role of e-commerce in mitigating the location and gender specific barriers to SME growth. Therefore, it is the aim of this study to address such gap in the literature, as well as to identify strategy that can be used to stimulate the development of female-owned SMEs in urban and rural developing countries, using Indonesia as case study.